Entrepreneurship and welfare - Jagannadha Pawan Tamvada (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
We examine returns to entrepreneurship using a standard measure of welfare, the percapita consumption expenditure. The analysis, using quantile regressions, reveals the existence of a welfare hierarchy in occupations. The results suggest that, across the welfare distribution, entrepreneurs who employ others have the highest returns in terms of consumption, while those entrepreneurs who work for themselves, that is, selfemployed individuals, have slightly lower returns than the salaried employees. However, self-employment entails higher returns than casual labor and a relative escape from poverty.
Keywords: J24; J43; J44; L26; 330; entrepreneurship; self-employment; welfare; developing countries; quantile regressions